Relationship between mean platelet volume and ischemic stroke in patients with patent foramen ovale - Nermin Bayar; Selçuk Küçükseymen; Zehra Erkal; Ramazan Güven; Erkan Köklü; Çağın Mustafa Üreyen; Şakir Arslan (KARE Publishing, 2017)
Objective: Patent foramen ovale (PFO) is commonly encountered in patients with cryptogenic stroke. Mean platelet volume (MPV), an indicator of platelet reactivity, has been reported in recent trials to be higher in patients with PFO than in normal population. The aim of this study was to investigate whether there is a difference in MPV between patients with PFO and stroke or transient ischemic attack (TIA) and that of patients with asymptomatic PFO. Methods: Patients with PFO who were younger than 55 years of age were enrolled in this retrospective study. Hemogram parameters of patients with ischemic stroke or TIA (symptomatic group) were obtained during hospitalization once they had stable clinical status. Results: Total of 108 patients, 51 of whom were symptomatic, were included in the study. MPV was determined to be higher in symptomatic group compared with asymptomatic group (median 10.0 fl [25th-75th percentile: 9.0-11.0] vs median 8.56 fl [25th-75th percentile: 8.0-9.0], respectively; p<0.001,. Cut-off point of 9.0 fl for MPV had 70% sensitivity and 86% specificity in predicting symptomatic PFO patients.  Conclusion: MPV is higher in symptomatic than in asymptomatic PFO patients. This finding may be a subsidiary risk factor to identify patients with PFO and high risk of cardioembolic stroke.